2010
DOI: 10.1086/648612
|View full text |Cite
|
Sign up to set email alerts
|

RtxA1‐Induced Expression of the Small GTPase Rac2 Plays a Key Role in the Pathogenicity ofVibrio vulnificus

Abstract: Infection with the human pathogen Vibrio vulnificus leads to the generation of reactive oxygen species (ROS) via NAD(P)H oxidase (Nox) in host cells. In the present study, we employed mutant V. vulnificus strains to identify an essential virulence factor responsible for this ROS generation. We found that repeats-in-toxin A1 (RtxA1) expressed by V. vulnificus acts via Nox1 to induce significant ROS generation in the intestine epithelial cells, which ultimately results in cell death. Furthermore, RtxA1 modulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…It has been reported that ROS induce the expression of E. coli iscR (9,10,12), and the host epithelial cells infected with V. vulnificus generate ROS (28). Therefore, we hypothesized that the induction of iscR expression upon exposure to INT-407 cells could result from the increased level of ROS generated from the host cells.…”
Section: Effects Of Host Cells On Iscr Expression Expression Of Iscrmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been reported that ROS induce the expression of E. coli iscR (9,10,12), and the host epithelial cells infected with V. vulnificus generate ROS (28). Therefore, we hypothesized that the induction of iscR expression upon exposure to INT-407 cells could result from the increased level of ROS generated from the host cells.…”
Section: Effects Of Host Cells On Iscr Expression Expression Of Iscrmentioning
confidence: 97%
“…When necessary, the wild-type V. vulnificus grown to A 600 0.5 was exposed to MEMF (control), hydrogen peroxide (H 2 O 2 ), INT-407 cells, or INT-407 cells preincubated with 25 mM N-acetyl-L-cysteine (NAC) for 1 h to scavenge reactive oxygen species (ROS) (28). For H 2 O 2 exposure experiments, V. vulnificus was grown anaerobically as described elsewhere (29).…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…This attenuated virulence of the prx3 mutant suggested that Prx3 is essential for the pathogenesis of V. vulnificus. Recent work also has shown that the cells of mouse intestine infected with V. vulnificus generate ROS (45). Therefore, it is reasonable to assume that Prx3 could contribute to the pathogenesis by protecting the pathogen from the ROS imposed by host cells to ensure its survival and multiplication during infection.…”
Section: Prx3 Is Essential For Survival Under Oxidative Stress and VImentioning
confidence: 99%
“…In fact, V. vulnificus accounts for 1% of all food-related deaths in the United States (4). Numerous studies recently have described a V. vulnificus multifunctional-autoprocessing RTX toxin (MARTX Vv ) as having a major impact on virulence in mice (5)(6)(7)(8). Toxins of the MARTX family are very large composite toxins.…”
mentioning
confidence: 99%